Pengaruh Sosial Media Marketing Instagram terhadap Keputusan Pembelian Kuliner UMKM - Nurita Elvira; Neila Susanti; Abdul Rasyid (Multiverse: Open Multidisciplinary Journal, 2023)
This article aims to examine the effect of social media marketing via Instagram on MSME culinary buying decisions. In the digital era, lifestyle is influenced by something that is trending and viral. The use of social media in obtaining information is the most important stage for making purchasing decisions. One of the marketing media that is currently in great demand by Micro, Small and Medium Enterprises (MSMEs) for sales promotion media is social media marketing. The business marketing strategy carried out by MSME actors by utilizing Instagram to do business by uploading the product content they are marketing is persuasive in nature which can attract buyers. This article uses a quantitative descriptive research method, data collection is done by distributing questionnaires through the Google form. The results of the study show that content sharing, connected has a positive and significant effect on purchasing decisions. But content creation, community building has a positive but not significant effect on purchasing decisions so that the hypothesis proves the truth. The partial results (t test) show that the content sharing variable contributes the most dominantly to purchasing decisions. Meanwhile, simultaneously (F test) shows that creating content, sharing content, connecting, building a community together (simultaneously) has a significant effect on purchasing decisions.